An evergrowing sweet cherry for research and breeding - Hedhly, Afif; Martínez-Romera, Nerea; Gracia, Ana Pilar; Marin, Juan; Arbeloa, Arancha; García, Elena; Wünsch, Ana (Frontiers in Plant Science, 2025)
Evergrowing phenotypes in deciduous trees have only been described in three unrelated species: peach, hazelnut and pomegranate. These genotypes are a useful tool for forward genetics approaches aimed at understanding the processes that regulate seasonal growth and dormancy. Research in evergrowing peach lead to the identification of the DORMANCY ASSOCIATED MADS BOX transcription factors (DAMs) as regulators of dormancy in stone and pome fruits. In this work we present the breeding and preliminary characterization of an evergrowing (evg) sweet cherry genotype. This individual was obtained from in vitro embryo rescue of self-fertilization seeds, of a local self-compatible landrace. Unlike wild type sweet cherry, evg sweet cherry does not set buds in autumn and continues to grow throughout the winter. In contrast to evergrowing peach, no major structural deletion was observed in the tandemly arranged PavDAMs genes. However, specific expression profiles of these genes were observed in the evg sweet cherry. The specific polymorphisms previously observed in the PavDAMs of the parental cultivar, and the high level of inbreeding depression resulting from self-fertilization, suggest that the expression of homozygous recessive alleles might be the cause of the evergrowing phenotype. Ongoing work to fully characterize the underlying molecular mechanism regulating evg sweet cherry phenotype is discussed, highlighting its importance and utility as a research and breeding tool.